Investigation of IrO2/Pt Electrocatalysts in Unitized Regenerative Fuel Cells - V. Baglio; C. D'Urso; A. Di Blasi; R. Ornelas; L. G. Arriaga; V. Antonucci; A. S. Aricò (International Journal of Electrochemistry)
IrO2/Pt catalysts (at different concentrations) were synthesized by incipient wetness technique and characterized by XRD, XRF, and SEM. Water electrolysis/fuel cell performances were evaluated in a 5 cm2 single cell under Unitized Regenerative Fuel Cell (URFC) configuration. The IrO2/Pt composition of 14/86 showed the highest performance for water electrolysis and the lowest one as fuel cell. It is derived that for fuel cell operation an excess of Pt favours the oxygen reduction process whereas IrO2 promotes oxygen evolution. From the present results, it appears that the diffusion characteristics and the reaction rate in fuel cell mode are significantly lower than in the electrolyser mode. This requires the enhancement of the gas diffusion properties of the electrodes and the catalytic properties for cathode operation in fuel cells.